The Iconography of Jewish Vilna during the First World War - Laučkaitė, Laima (Colloquia, 2021)
The aim of the article is to show the picture of Jewish Vilnius/ Vilna created by German artists during the First World War. The research is based on an analysis of works of art published in the press of the time, or stored in institutions in Lithuania, Germany and Belgium, and also on an analysis of writings in German periodicals of that time. The media in Ober Ost during the war took an anti-semitic stance, promoted by the top military leadership, but the author of the article argues that there also existed a different attitude towards the Jews of Vilnius and their heritage. The views and origins of journalists, writers and artists taken on by the editorial boards of German newspapers published in Vilnius and Kaunas influenced the emergence of the Ostjuden discourse. This discourse was rather contradictory, and included both fascination with the traditional religious Jewish community, and its cultural heritage and spiritual values, and at the same time horror at the suffering and poverty of the community. This discourse also remained viable in postwar Germany, and influenced the identity of Jewish art in Vilnius in the interwar period.